The Chicken Metaphor in The Creation of Painting Works - Kunto Adi Rumekso (UNIVERSITAS SERAMBI MEKKAH, 2024)
This study aimed to examine the creation of paintings with chicken as the subject. The results of the study showed that chickens are animals that have close relationships with humans, both in everyday life and in culture. Chickens also have symbols that can be interpreted broadly, such as courage, struggle, independence, and so on. In paintings, chickens can be visualized in a variety of styles, from realistic to abstract to expressionism. The use of chicken visuals in painting can be packaged in a variety of themes, such as everyday life, culture, and symbolism. In conclusion, chickens are an interesting subject to be used as a theme in paintings. Paintings with chicken as the subject can be a means of expressing oneself and the ideas that exist within oneself.